CBCT of maxillary central incisor with internal resorption: a case report - Khamila Gayatri Anjani; Fahri Reza Ramadhan; Azhari Azhari (Jurnal Radiologi Dentomaksilofasial Indonesia (JRDI), 2021)
Objectives: The aim of this case report is to report the radiographic features of an internal resorption in maxillary central incisor and to emphasize the benefits of CBCT in this case. Case Report: A 14-year-old male went to Universitas Padjadjaran Dental Hospital with a discoloration of his fracture upper anterior teeth. The anamnesis revealed that the patient had history of a fall in about 6 years ago. Patient didn’t complain about pain when examination happened and wanted to have his teeth treated. Periapical radiograph showed an internal resorption in maxillary central incisor. Cone beam computed tomography (CBCT) was used to see other findings before determining the treatment plan. Conclusion: Internal resorption gives a characteristic appearance on the radiograph. CBCT modalities provide more information than conventional ones so that the use of this modality is not only to establish a diagnosis, but also can be used in determining the right treatment plan.